2017
DOI: 10.1111/jcmm.13199
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic roles of telocytes in OVA‐induced acute asthma in mice

Abstract: Telocytes (TCs) newly discovered as the mesenchyme‐derived interstitial cells were found to have supportive effects on mesenchymal stem cells (MSCs). The present study aimed at investigating effects of TCs or TCs gathered with MSCs on experimental airway inflammation and hyper‐responsiveness. The TCs were isolated from the lung tissue of the female BALB/c mice. The ovalbumin (OVA)‐induced asthma model was established. TCs (1 × 106/2 × 106) and/or MSCs (1 × 106) were injected through mice tail vein for consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Inflammatory factors are deeply involved in LPSinduced apoptosis and injury, and could be regulated by ROS [25]. Secreting IFN-γ to induce the differentiation of naive CD4 + T cells into Th1 cells had been considered for TCs to improve allergen-induced airway inflammation and hyper-responsiveness [7]. Our current study demonstrated that TCs reversed LPS-induced IL-6 expression in HaCaT cells, HDMECs, and L929 cells.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Inflammatory factors are deeply involved in LPSinduced apoptosis and injury, and could be regulated by ROS [25]. Secreting IFN-γ to induce the differentiation of naive CD4 + T cells into Th1 cells had been considered for TCs to improve allergen-induced airway inflammation and hyper-responsiveness [7]. Our current study demonstrated that TCs reversed LPS-induced IL-6 expression in HaCaT cells, HDMECs, and L929 cells.…”
Section: Discussionmentioning
confidence: 54%
“…TCs are distinguished from other interstitial cell types, including stem cells and fibroblasts, by protein profiles and gene profiles [6]. Many studies have found that TCs can exert a substantial impact on regeneration and repair, for example, reducing myocardial infarction and acute lung injury [7]. TCs can affect other adjacent cells via direct connection or indirect modes by producing and releasing materials and molecules, including extracellular vesicles, and they are particularly involved in cell-to-cell communication [8].…”
Section: Introductionmentioning
confidence: 99%
“…Telocytes in mammals have also been intensely studied. They have been detected in livestock, such as sheep (Abd-Elhafeez et al 2017), in pets, like dogs (Xu et al 2016), and in laboratory animals, like guinea pigs (Nguyen et al 2011), rats (Hatta et al 2012) and mice (Ye et al 2017). Moreover, telocytes have been found also in invertebrates; in 2017, the presence of telocytes was confirmed in leeches (Hirudo medicinalis) (Pulze et al 2017).…”
Section: Question 4 Are Telocytes Described Exclusively In Humans?mentioning
confidence: 99%
“…In recent years, researchers have used focused ion beam scanning electron microscopy to investigate the 3D imaging of TCs in human dermis, and have revealed the existence of Tps with various conformations: (i) long, flattened irregular veils (ribbon-like segments) with knobs, corresponding to podoms, and (ii) tubular structures (podomers) with uneven calibre because of irregular dilations (knobs) -the podoms 10 . So far, TCs have been detected in many tissues and organs, including the heart 11,12 , lung 13,14 , skeletal muscle 15 , skin 16,17 , eye 18,19 , liver 20 , uterus 21 and urinary system 22,23 .…”
mentioning
confidence: 99%